Discipline and Autonomy in Extracurricular Sports Activities in Japan: 'Coach Discourse' in the 2000s. Issue 1 (2nd January 2022) - Shimotake, Ryoji
Abstract: This study describes how 'discipline' and 'autonomy' as educational techniques were transformed after 2000 via analysis of Japan's 'coach discourse'. It considers the autobiographies of extracurricular sports coaches in Japan, mainly those published during the period and not extensively analyzed in previous studies. Coaches were perplexed by students' changing characters and paid attention to the balance between 'discipline' and 'autonomy', resulting in a leadership style that separated students' daily life from sports, enforcing 'discipline' in the former and advocating 'autonomy' in the latter. This encouraged 'autonomy' and self-discipline in students and furthered personal development via acceptance of the 'enjoyment' that came from overcoming the strict and harsh nature of sport practice, while encouraging them to become 'independent'. In this way, a new educational technique emerged in Japan's extracurricular sports activities of the 2000s; one that preserves the students' freedom to the greatest extent within sport, while skillfully controlling conduct by enforcing 'discipline' in their daily lives. The significance of this study is in analyzing the relationship between 'discipline' and 'autonomy', which has not been discussed in previous studies, from the perspective of Michel Foucault's 'the game of freedom and security'.